Gamochaeta falcata (Lam.) Cabrera (Compositae, Gnaphalieae) in Tunisia, a first official record for the African continent - El Mokni, Ridha (UMA Editorial, 2025)
Gamochaeta falcata (Asteraceae, Gnaphalieae), a species native to southern America, is reported here for the first time to the African Gnaphaliinae from a collection made in northwestern Tunisia. Based on a review of relevant literature, a brief morphological description is provided, along with information on phenology and original photographs of the Tunisian specimen. Moreover, some data on the habitat and current distribution of this neophyte are presented.

Se cita aquí la especie Gamochaeta falcata (Asteraceae, Gnaphalieae), originaria del sur de América, como una Gnaphaliinae nueva para el continente africano, a partir de una recolección efectuada en el noroeste de Túnez. Se ha llevado a cabo un análisis de literatura relevante que ha permitido elaborar una breve descripción de la planta. Se aportan, además, datos fenológicos y fotografías originales del material tunecino y se describe su hábitat, así como la distribución actual de este neófito.
Gamochaeta falcata (Lam.) Cabrera (Compositae, Gnaphalieae) en Túnez, primer registro oficial en el continente africano
Keywords: Plantas - Clasificación; Fitogeografía; Compuestas - África; Chorology; New records; Neophyte; Africa